2023
DOI: 10.1002/jev2.12320
|View full text |Cite
|
Sign up to set email alerts
|

MitoEVs: A new player in multiple disease pathology and treatment

Abstract: Mitochondrial damage plays vital roles in the pathology of many diseases, such as cancers, neurodegenerative diseases, aging, metabolic diseases and many types of organ injury. However, the regulatory mechanism of mitochondrial functions among different cells or organs in vivo is still unclear, and efficient therapies for attenuating mitochondrial damage are urgently needed. Extracellular vesicles (EVs) are cell‐derived nanovesicles that can deliver bioactive cargoes among cells or organs. Interestingly, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…S5F ). For example, four members of NADH dehydrogenase (Ndufa2, Ndufa7, Ndufs5, and Ndufv3) were all uniquely present in the BMEF (Table S3 ), indicating specific extracellular function for these metabolic enzymes in BMEF and possible unique regulation of the leukemia microenvironment of adults, as suggested for other cancers [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…S5F ). For example, four members of NADH dehydrogenase (Ndufa2, Ndufa7, Ndufs5, and Ndufv3) were all uniquely present in the BMEF (Table S3 ), indicating specific extracellular function for these metabolic enzymes in BMEF and possible unique regulation of the leukemia microenvironment of adults, as suggested for other cancers [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, mitochondrial respiratory defects and mtROS overproduction under hyperglycemic conditions induce NF-κB/p38 MAPK pathway and cytokine (e.g., TNF-α and IL-6) production in Mφs ( 41 ). Likewise, mitochondrial stress caused by mitochondrial Lon overexpression promoted the secretion of EVs harboring mtDNA in cancer cells ( 44 ). Consistently, M1-Mφs in the GLN − group exhibited impaired mitochondrial oxidative metabolism, as indicated by increased mtROS and decreased mitochondrial membrane potential and ATP compared to those in the GLN + group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EVs are essential intercellular communication vectors for the transfer of bioactive substances between cells and organs. Recently, abundant evidence has shown that mitochondria-derived vesicles (MDVs, ~70-150 nm) or intact mitochondrial translocation is mainly mediated by multivesicular bodies (MVBs, ~30-150 nm) and MVs (~200-1000 nm) and that vesicle formation as well as release cannot be separated from the role of endocytosis in cells [28]. We used dynasore to inhibit the formation and release of MVBs and MVs, thereby inhibiting mitochondrial transfer and reception.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that some subtypes of extracellular vesicles (EVs) can carry mitochondrial components from cell to cell (i.e., mitoEVs) and that complete parallel transfer of mitochondria can occur via MVs [28]. Dynasore, an inhibitor of the endocytic pathway, rapidly blocks the formation of coated vesicles, thereby preventing the delivery and reception of mitochondria as MVs.…”
Section: Inhibitor Dose Effects On Mitochondrial Transfermentioning
confidence: 99%